Effects of Lime, Vermicompost, and Chemical P Fertilizer on Selected Properties of Acid Soils of Ebantu District, Western Highlands of Ethiopia - Abdissa Bekele; Kibebew Kibret; Bobe Bedadi; Markku Yli-Halla; Tesfaye Balemi (Applied and Environmental Soil Science)
Soil acidity is one of the major factors limiting soil fertility and crop production in large areas of Ethiopia. A two-month incubation experiment was conducted to evaluate the effects of lime, vermicompost (VC), and chemical phosphorus (P) fertilizer on selected chemical properties of Dystric Nitisols in Ebantu District, Western Ethiopia. The treatments comprised of three rates of lime (2, 4, and 6 tons CaCO3·ha−1), VC (2.5, 5, and 7.5 tons·ha−1), and mineral P fertilizer (20, 40, and 60 kg·P·ha−1) each applied alone and in various combinations. The experiment was laid down in a completely randomized design with two replications. The results showed that the highest increment of pH from 4.83 at the control to 6.05 and reduction of exchangeable Al from 1.70 to 0.09 cmolc·kg−1 were obtained from combined application of lime at 4 tons CaCO3·ha−1 and VC at 7.5 tons·ha−1. The most significant decrease in exchangeable acidity (0.17 cmolc.kg-1) was observed in soil that was treated with 6 tons CaCO3·ha−1 lime applied alone (93%) and combined application of lime at 4 tons CaCO3·ha−1 with VC at 7.5 tons·ha−1 by (81%). The highest contents of OM (4.1%) and total nitrogen (0.29%) were obtained from combined application of lime at 4 tons CaCO3·ha−1 and VC at 7.5 tons·ha−1. Integrated application of chemical P (60 kg·P·ha−1) with lime (2 tons·ha−1) plus VC (7.5 tons·ha−1) resulted in Bray-II P increased by 45% relative to control. The various combinations of the treatments also improved exchangeable Ca2+ and Mg2+. The results indicate that integrated use of lime, vermicompost, and chemical P fertilizer can improve soil acidity and availability of nutrients. However, the real potential of the amendments used in this experiment should be further assessed under field conditions using a test crop.